Becoming good American schools : - Oakes, Jeannie (Jossey-Bass, 2000)
This book tells the stories of sixteen schools in California, Illinois, Massachusetts, Texas, and Vermont that sought to alter their structures and practices and become places fostering innovative ideas, caring people, principles of social justice, and democratic processes. Based on longitudinal, comparative case-study research, these accounts attest to the power of committing to public virtue and the struggle of educators to transform that commitment into changed school practice. The authors argue that better schools will come only when policy makers, educators, and citizens move beyond technical and bureaucratic reforms to engage in the same educative, socially just, caring, and participatory processes they want for schoolchildren. Those processes constitute betterment--both the means and the ends of school reform. Becoming Good American Schools is for administrators, policy makers, practitioners, and citizens who are prepared to blend inspiration and caution, idealism and skepticism in their own pursuit of good schools.